A Satire on Capitalism in Don DeLillo’sCosmopolis - Sudibyo, Gabriel (LANTERN (Journal on English Language, Culture and Literature), 2014)
The aim of this final paper is to identify the issue of capitalism in Don DeLillo’sCosmopolis through Marxism theory. The writer uses book reading method to understand the theory well, internet browsing and note-taking method were also used to collect further information regarding Marxism. From the intrinsic elements, only the characters, setting, and conflicts are analyzed. The extrinsic element will contain issues of capitalism. The writer focuses specifically only on three aspects from Marxism theory: false consciousness, alienation, and class-struggle. The writer also analyzes how the capitalism effects are being satirized to criticize capitalism itself. The result shows that capitalism issue within the novel has its effects implanted in the protagonist’s life and the author succeeds in satirizing the story into a good irony compared to real life situation.